A comparative history of ideas - Nakamura, Hajime (KPI, 1986)
Hajime Nakamura argues that particular intellectual and social developments can be traced in all great cultures; that each culture deals with its problems in about the same order. Discussing ideas from India, China, Japan and Europe, the author considers such inclusive notions as the concept of God.